The Effects of Different Periods of Shading on Growth and Yield in 'Sweet Charlie' Strawberry - Demirsoy, L.; Demirsoy, H.; Uzun, S.; Öztürk, A. (Int Soc Horticultural Science - ISHS, 2007)
In this study, the effects of shading treatments at different time periods on yield and growth in the Junebearing strawberry 'Sweet Charlie' were evaluated. The plants were covered with 50 % shading material in a greenhouse during the following periods: 1) greenhouse check (GC), no shade, 2) flower initiation period (FIPl) in Fall 2002, 3) flower initiation period (FIP2) in Fall 2002, 4) the fruiting period (FP) in Spring 2003, 5) constant shading (CS), 6) open field (OF), no shade. Shading during the FP reduced runnering. In general, there was no consistent effect of shading on the crown and leaf number in the experiment. The leaf area of the plants in the CS treatment was generally larger than that in the other treatments in the spring and summer period. Also, the petiole length of the plants in GC and CS was higher than that of the plants in OF in the spring and summer periods. Yield was significantly reduced in the FIPl and FIP2 treatments. Shading during FP reduced inflorescence number and yield. CS significantly reduced all of the yield parameters. In OF, the number of inflorescences and flowers and the yield per plant was significantly reduced compared to other treatments possibly because of lower temperature preventing flowering or injuring the flowers. The increased fruit weight with CS and OF treatments was the result of reduced inflorescence and flower numbers. Fruit was the smallest in FIPl. The soluble solid content of the fruits in OF was the highest possibly due to the high light intensity while those of the fruits in CS and FP was the lowest. The amount of discarded fruit (deformed, rotten and small fruit) on plants shaded during FP was the highest while the least amount of total discarded fruit was from plants in the open field. In summary, the results of the study suggest that 'Sweet Charlie' responded negatively to shading. © Verlag Eugen Ulmer KC.
Keywords: 'Sweet Charlie'; Growth; Quality; Shading; Strawberry; Yield